Heuristic Evaluation of German Language Mobile Learning Applications Among Indonesian University Students - Syarifah Fatimah; Muftihaturrahmah Burhamzah; Alamsyah; Sabrina Saiidi (Journal of Vocational, Informatics and Computer Education, 2025)
Purpose – Despite the growing availability of German language mobile learning applications, no empirical usability evaluation targeting Indonesian university students enrolled in German Language Education study programmes has been reported. This study evaluates the usability of three mobile applications used in German language learning two commercial apps and one campus-developed app using Nielsen's (1994) heuristic evaluation framework. Methods – A heuristic evaluation was conducted by 25 student evaluators trained in Nielsen’s ten usability heuristics. Each evaluator independently rated usability problems on a 0–4 severity scale across three apps: Duolingo (App A), Babbel (App B), and a campus-developed mobile LMS (App C). Evaluators also completed the System Usability Scale (SUS). Data were analysed using descriptive statistics and the Friedman test with Wilcoxon signed-rank post-hoc comparisons (α = .05), appropriate for the repeated-measures design in which the same 25 evaluators assessed all three applications.  Findings – The campus app (App C) yielded the highest overall mean severity score (2.09) with 90 usability problems identified, predominantly in the Minor to approaching-Major severity range (mean scores 1.5–2.8 on Nielsen’s 0–4 scale). The most severe violations involved Help and Documentation (H10: M = 2.8) and Flexibility and Efficiency of Use (H7: M = 2.6). SUS scores were: App A = 82.4 (Good), App B = 74.8 (Good), App C = 51.6 (OK). Within-evaluator differences across the three applications were statistically significant for both severity (Friedman χ²(2) = 38.42, p < .001, W = .77) and SUS (Friedman χ²(2) = 34.88, p < .001, W = .70), with large effect sizes. Research implications – Findings are limited by the use of trained student evaluators rather than expert usability professionals, a single-institution sample, and the absence of summative user testing with actual German language learning tasks. The simulated evaluation context may not capture all real-world interaction patterns. Originality – This study is the first to apply Nielsen's heuristic evaluation framework to German language mobile learning applications in the Indonesian higher education context. It provides an empirically grounded usability problem list and design recommendations specifically relevant to campus-developed German language learning apps, contributing to both HCI research and German language education technology practice.